Etika dan Moral dalam Penanganan Orang dengan Gangguan Jiwa dalam Perspektif Islam - Salmaa Alfisyah Faza; Firda Noor Rahmatin; Aisha Halwa Nazhifa (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
Handling of people with mental disorders has received serious attention from various perspectives, including in Islam which views it with a comprehensive view. The background of this study focuses on how Islam instructs its followers to treat individuals with mental disorders, as well as the humanitarian values ​​emphasized by religion in the aspect of handling. The purpose of this study is to explore the Islamic view on handling people with mental disorders, and to gain a deeper understanding of the guidance given by Islam in this regard. The research method is a literature review that critically examines the body of academic literature. The nature of this study is descriptive analysis, where related data is systematically and orderly analyzed to provide a good understanding to the reader. Qualitative data in the form of written language was obtained from journals and articles, and analyzed through a concise content analysis. The findings of the study indicate that Islam provides strong ethical guidance as well as practical behavior in handling individuals with mental disorders, which can make a positive contribution to the modern approach in psychiatry and mental health services. The implications of this study provide new insights into the integration of mental health approaches with religious values ​​that offer a holistic approach to the individual.